Characteristics of Scavengers With Skin Diseases in Wukirsari Landfill, Gunung Kidul, Yogyakarta - Mulasari, Surahma Asti; Novianingrum, Novianingrum (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Skin diseases are disorders of the skin caused by fungi, bacteria, parasites, viruses, and infections. Based on the health profile of Indonesia 2010, the number of acquired skin disorder cases in Indonesia was 122076 cases. This study aimed to determine the relationship between the characteristics of scavengers and the incidence of skin diseases at the land-fill at Wukirsari Gunung kidul Yogyakarta. The study design was cross-sectional. The samples were 32 Wukirsari Gunungkidul land-fill scavengers and selected through totality sampling. The data was analyzed using chi square test. Measurement instruments used were questionnaires, checklists sheet, and doctor’s diagnosis. The result showed that there was a statistically significant relationship between personal hygiene and skin disease incidence (p =0.005; RP=3.193) and between usage of personal protective equipment (PPE) and skin disease incidence (p =0.001; RP=3.086), while there was no statistically significant relationship between skin disease and working duration (p =0.755; RP=1.111).